Food marketing to teenagers: Examining the power and platforms of food and beverage marketing in Canada. (1st June 2022) - Elliott, Charlene; Truman, Emily; Aponte-Hao, Sylvia
Abstract: Marketing pressure on teenagers when it comes to promoting unhealthy foods and food brands is a significant public health concern. Teenagers are aggressively targeted by food marketing messages, yet a research gap exists when it comes to the engagement by teens with this marketing in real world settings, and specific techniques (or power) used to capture their attention. This exploratory study engages in participatory research to explore the persuasive power and platforms of exposure of teen-targeted food marketing. Using an innovative smartphone app called "GrabFM!" ("Grab Food Marketing!"), teens ages 13–17 (n = 62) identified and tagged examples (n = 339) of targeted food marketing (from mainstream and digital media, and the built environment) over a 7-day period, providing information on the food brand, product, platform, and indicators (i.e., persuasive techniques). Results revealed the top brand (FritoLay, 8.3%), food product category (candy/chocolate, 23.3%), platform of exposure (Instagram, 76.4%), and indicator (visual style, 52.5%) identified by teens. Insights were also gained into the intersection of gender and platform, gender, age and indicators (older teens 15+ more likely to report multiple indicators per ad), and co-occurrence of indicators (majority of ads tagged with one indicator only). The results of this study provide guidance on the power, platforms and brands that teens felt uniquely spoke to them. When it comes to monitoring efforts, it is useful to know that Instagram commands teenagers' attention and that marketing power resides in particular indicators (visual style, special offer, theme), which teenagers appear to readily and consistently identify.